2023
DOI: 10.1039/d2cp05479e
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Eley–Rideal recombination of hydrogen atoms on Cu (111)viaa high-dimensional neural network potential energy surface

Abstract: As a prototypical system for studying the Eley-Rideal (ER) mechanism at the gas-surface interface, the reaction between incident H/D atoms and pre-covered D/H atoms on Cu(111) has attracted much experimental...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…Fortunately, recent QCT calculations with electronic friction based on a multiadsorbate neural network potential suggested that these effects are not significant. 50 Nevertheless, the predicted vibrational state distribution remained too cold compared to the experiment. Apparently, the disagreement between theory and experiment in this aspect remains unsolved, and the origin is not clear.…”
Section: Product State Distributions Figure 3 Compares the Internal S...mentioning
confidence: 92%
See 2 more Smart Citations
“…Fortunately, recent QCT calculations with electronic friction based on a multiadsorbate neural network potential suggested that these effects are not significant. 50 Nevertheless, the predicted vibrational state distribution remained too cold compared to the experiment. Apparently, the disagreement between theory and experiment in this aspect remains unsolved, and the origin is not clear.…”
Section: Product State Distributions Figure 3 Compares the Internal S...mentioning
confidence: 92%
“…One reason for using this empirical PES is to enable direct comparison of present single-adsorbate results with previous multiadsorbate QCT results, 54 which were obtained by the same PES. We also have a neural network-based PES at hand, 50 which, however, contains two adsorbates in the supercell, while the current QD implementation can only deal with the single-adsorbate case.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive hydrogen chemistry at surfaces plays an important role in key heterogeneous catalysis processes such as the Haber–Bosch process , or methanol synthesis. Copper is a particularly interesting metal to study in this context due to its widespread use as a catalyst in many chemical reactions. Consequently, the dissociation of hydrogen on Cu surfaces has become a benchmark problem for experimental and theoretical research.…”
Section: Introductionmentioning
confidence: 99%
“… 6 8 Copper is a particularly interesting metal to study in this context due to its widespread use as a catalyst in many chemical reactions. Consequently, the dissociation of hydrogen on Cu surfaces has become a benchmark problem for experimental 9 17 and theoretical 18 34 research.…”
Section: Introductionmentioning
confidence: 99%